Deformation behavior of multilayered Al–Cu clad composite during cold-swaging. (15th January 2016) - Kocich, Radim; Kunčická, Lenka; Davis, Casey F.; Lowe, Terry C.; Szurman, Ivo; Macháčková, Adéla
Abstract: Deformation behaviors during swaging of an Al/Cu/Al layered clad composite were investigated experimentally and by finite element (FE) analysis. Measured and predicted deformation responses were compared and found to be in generally good agreement. These comparisons also validated the design and operation of a custom device that measures the total force required for swaging. An average effective strain of 0.5 was predicted for the first swaging pass, but the strain distribution was significantly inhomogeneous. Predicted strain gradients and stresses were consistent with experimentally observed gradients in grain size and subgrain size. The highest flow stresses were predicted in the Cu layer, where the measured subgrain size was correspondingly small. The predicted gradients in temperature and strain also correlated well with the observation of recrystallization in the outer Al layer. Graphical abstract: Highlights: Verification of our newly designed swaging force measuring device was performed. Strain distribution in the layers within the composite during a pass was predicted. Plastic flow of individual layers was predicted and differences were explained. Microhardness increased after swaging and corresponded to the predicted strain. Microstructure analyses showed significant grain refinement and subgrains formation.